Can L-Carnitine Replace Tumor Necrosis Factor-Alpha Blockers? A Systematic Review and Dose-Response Meta-Analysis - Farnaz Naeimzadeh; Amirreza Naseri; Sarvin Sanaie; Seiedhadi Saghaleini; Afshin Gharekhani (Tabriz University of Medical Sciences, 2024)
Background: L-carnitine (LC), an amino acid-like molecule, has been shown to reduce tumor necrosis factor-alpha (TNF-α), although some research has not confirmed its impact. This study aimed to identify the effects of LC supplementation on TNF-α levels through a systematic review and meta-analysis of randomized controlled trials (RCTs). Methods: This study followed the PRISMA 2020 statement and searched the Web of Science, PubMed, Embase, and Scopus for related papers on LC supplementation's effects on TNF-α in adults. The meta-analysis was performed using the 17th version of the Stata Statistical Software, and the I2 statistic was used to assess the impact of heterogeneity. The Cochrane risk of bias tool was used to evaluate the risk of bias in the included studies. Results: Seventeen RCTs were included based on the full-text review, and the data from 14 studies were included in the meta-analysis. Based on the results, oral LC did not have a significant impact on TNF-α levels (Cohen's d: -0.19 [95% CI: -0.71 to 0.33]; I2 : 97.39%). However, parenteral LC had significantly reduced TNF-α levels (Cohen's d: -1.60 [95% CI: -3.06 to -0.15]; I2 : 88.92%). Oral LC doses of 0.75 and 6 g/day were effective, while duration of LC administration was associated with significant findings in 2, 36, and 48 weeks. The dose and duration of LC administration ineffective independently of TNF-α levels (P = 0.35 and P = 0.70 for dose and duration of administration, respectively). Conclusion: In this meta-analysis, oral LC supplementation failed to be superior to TNF-α blockers.